Pengaruh Rasio Keuangan, Komite Audit, dan Tata Kelola Perusahaan terhadap Financial Distress - Hanny Hanny; Aan Marlinah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to obtain empirical evidence about the influence of leverage, liquidity, profitability, sales growth, operating capacity, proportion of independent commissioners, size of audit committee, managerial ownership and frequency of audit committee meetings as independent variables on financial distress as dependent variable. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The study used purposive sampling with total 63 companies and 189 research data. This study uses multiple regression methods to examine variables that affect financial distress measured using the Altman Z-score. The results of this study indicate that Profitability, Operating Capacity, Proportion of Independent Commissioners, and Managerial Ownership have an influence on Financial Distress. While, Leverage, Liquidity, Sales growth, Size of Audit Committee, and Frequency of Audit Committee Meetings have no effect on Financial Distress.